2021
DOI: 10.47059/alinteri/v36i2/ajas21128
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chironomid Larvae in Compare to Other Fish Foods on Growth Parameters and Body Protein of Two Economically Important Fishes

Abstract: With the increasing human population, the demand for healthy, nutritious but cheap food also increasing day by day. The product of aquaculture mainly fish is more efficient to improve global food security. Along with the seafood, the effort is going on for more production of freshwater fish. For that reason, proper growth and sufficient proximate principles in fish are essential with a low-cost but healthy fish diet. Trichogaster fasciata and, Heteropneustes fossilis were fed with fourth instar larvae of Chiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Belyakov et al (2018) also reported this insect as a very well-known organism in the hypersaline lake of Crimea. It will be a big achievement for the fisheries industry in the aquatic bodies of the coastal region, as it is already experimentally proven that the application of Chironomus larvae as food is good for the growth of both omnivorous and carnivorous fish, and its application enhanced the nutritional content of fishes (Nath et al, 2021(Nath et al, , 2022.…”
Section: The Monthly Pattern Of Population Density In Both Open and Cap-mentioning
confidence: 99%
“…Belyakov et al (2018) also reported this insect as a very well-known organism in the hypersaline lake of Crimea. It will be a big achievement for the fisheries industry in the aquatic bodies of the coastal region, as it is already experimentally proven that the application of Chironomus larvae as food is good for the growth of both omnivorous and carnivorous fish, and its application enhanced the nutritional content of fishes (Nath et al, 2021(Nath et al, , 2022.…”
Section: The Monthly Pattern Of Population Density In Both Open and Cap-mentioning
confidence: 99%